2013
DOI: 10.1073/pnas.1303558110
|View full text |Cite
|
Sign up to set email alerts
|

ETV4 promotes metastasis in response to activation of PI3-kinase and Ras signaling in a mouse model of advanced prostate cancer

Abstract: Combinatorial activation of PI3-kinase and RAS signaling occurs frequently in advanced prostate cancer and is associated with adverse patient outcome. We now report that the oncogenic Ets variant 4 (Etv4) promotes prostate cancer metastasis in response to coactivation of PI3-kinase and Ras signaling pathways in a genetically engineered mouse model of highly penetrant, metastatic prostate cancer. Using an inducible Cre driver to simultaneously inactivate Pten while activating oncogenic Kras and a fluorescent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
129
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 71 publications
9
129
0
1
Order By: Relevance
“…We previously showed that RASdependent RAL effector pathway activation in DU145 cells leads to the acquisition of bone metastasis (24). Although RAS mutations are rare in prostate cancer (26,27), RAS pathway activation correlates with prostate cancer progression, as demonstrated by analyses of patient samples for Ras transcriptomic signatures (28,29). Consistent with this, downstream pathway biomarkers of the RAS pathway activation, phospho-ERK and phosphoinositol 3-kinase (PI3K)/phospho-AKT signaling, increase during progression (18).…”
mentioning
confidence: 99%
“…We previously showed that RASdependent RAL effector pathway activation in DU145 cells leads to the acquisition of bone metastasis (24). Although RAS mutations are rare in prostate cancer (26,27), RAS pathway activation correlates with prostate cancer progression, as demonstrated by analyses of patient samples for Ras transcriptomic signatures (28,29). Consistent with this, downstream pathway biomarkers of the RAS pathway activation, phospho-ERK and phosphoinositol 3-kinase (PI3K)/phospho-AKT signaling, increase during progression (18).…”
mentioning
confidence: 99%
“…Although NPK cells expressing control and Etv4 shRNAs formed tumors in immunodeficient mice, those that expressed the Etv4 shRNA developed smaller and fewer metastases in the lung and liver. Together, the in vitro and in vivo data obtained in the mouse models, as well as that seen in the gene expression signatures of human tumors, strongly support a role for ETV4 in the metastasis of prostate cancer cells (6).…”
mentioning
confidence: 78%
“…However, as the disease progresses and androgen receptor (AR) dependence is lost, these genetic lesions cooperate with signaling pathways, such those mediated by pRB, RAS/RAF, and phosphatidylinositol 3-kinase (PI3K)/PTEN/AKT, which are altered in a more "global" sense to promote metastasis (5). In PNAS, Aytes et al (6) describe the temporal progression and the consequence of molecular activation of the PI3K and RAS signaling pathways during prostate cancer metastasis. Using a unique genetically engineered mouse model of prostate cancer that allows lineage tracing, the authors demonstrate that the spread of tumor cells is an early event that actually occurs well before the onset of metastasis.…”
mentioning
confidence: 99%
“…It is now well established that PEA3 transcription factors are involved in prostate tumors and Ewing's sarcoma, as well as in other tumors, as a result of chromosomal translocations with ETV4 (8). Among the key features often found to be dysregulated in advanced prostate cancer, the PI3K and Ras pathways are altered in 40% of primary tumors and in 90% of metastatic tumors, and the combined signaling activity of these two pathways promotes the metastasis of prostate cancer through activation of ETV4 (42,43). In a study of breast cancer in humans, a positive association was observed between the overexpression of ETV4 and HER2/neu overexpression, tumor grade and greater recurrence rates (8).…”
Section: Discussionmentioning
confidence: 99%